Muslim becoming : aspiration and skepticism in Pakistan - Khan, Naveeda Ahmed, 1969- (Duke University Press, 2012)
This thoughtful ethnography of Islam in Pakistan moves from the smallest scale-a single worshiper striving to be a better Muslim who is seeking guidance at a neighborhood mosque-to the largest, examining the thought of poet and philosopher Muhammad Iqbal, considered to be the spiritual visionary of the country.